Asuhan Keperawatan Pada Ny.S P2A1 Post Sectio Caesarea Dengan Indikasi Kala 1 Lama Di Ruang Mawar 2 Rsud Surakarta - Atmy, Malinda; , Sulastri, S.Kp., M.Kes (2015)
Background : The delivery prosess is a process of saving the lives of mother and babies. Later delivery method abdominal wall surgery (laparotomy) is now an option that must be lived as an emergency to save the mother babies. Or both or oven theconditionof a baby who has indications such as when one long / prolonged labor. Prolonged labor itself is one of the causes of maternal death and newborn. Objective : To determine the nursing care to clients eith post section caesarea with an indication of when the old one. Covering assessment, intervention, implementation, and evaluation of nursing. Results : After 3 days of nursing actions appear diagnosis is pain, barriers mobilization, and his lack of knowledge. Then, in the most correct implementation in accordance with plans that have been implemented. Conclusion : Cooperation between the health care team and patient / family is in need of nursing care for the success of the patient so that the patient's nursing problems regarding pain problems, obstacles mobilization, and its lack of knowledge can be done well and some of the problems solved in part to its conclusion. Keywords : Sectio caesarea, when one long, painful